CRYSTALLIZATION BEHAVIOR AND MICROMORPHOLOGY OF SOL-GEL DERIVED MESOPOROUS NANO-PARTICLES TITANIA - Silvester Tursiloadi; Hiroshi Hirashima; Yu Yamanakaz (Jurnal Sains Materi Indonesia, 2004)
CRYSTALLIZATION BEHAVIOR AND MICROMORPHOLOGY OF SOL-GEL DERIVED MESOPOROUS NANO-PARTICLES TITANIA. In this work, effects of drying methods on the micro-morphology ofinesoporpous TiO2 prepared by the sol-gel method has been studied using transmission electron microscopy (TEM), X-ray diffraction analysis (XRD) and N2 gas adsorption. Mesoporous TiO2 consists of anatase nano-particles, about 5nm in diameter, have been obtained by hydrolysis of titanium alkoxide in a methanol solution and supercritical extraction in CO2 at 60°C and 22Mpa. XRD peaks ofrutile have been found after annealing at 600°C. The particle sizes of anatase and rutile are about 13 and 25nm in diameter, respectively. The surface morphology of Ti02 nano-particles has been discussed with the surface fractal dimensions estimated from the N2 gas adsorption isotherms.